Olfaction in Anopheles mosquitoes. (22nd April 2021) - Konopka, Joanna K; Task, Darya; Afify, Ali; Raji, Joshua; Deibel, Katelynn; Maguire, Sarah; Lawrence, Randy; Potter, Christopher J
Abstract: As vectors of disease, mosquitoes are a global threat to human health. The Anopheles mosquito is the deadliest mosquito species as the insect vector of the malaria-causing parasite, which kills hundreds of thousands every year. These mosquitoes are reliant on their sense of smell (olfaction) to guide most of their behaviors, and a better understanding of Anopheles olfaction identifies opportunities for reducing the spread of malaria. This review takes a detailed look at Anopheles olfaction. We explore a range of topics from chemosensory receptors, olfactory neurons, and sensory appendages to behaviors guided by olfaction (including host-seeking, foraging, oviposition, and mating), to vector management strategies that target mosquito olfaction. We identify many research areas that remain to be addressed.